O Hino dos Libertinos : poesia marginal e ditadura no Brasil por meio da antologia “26 Poetas Hoje” de 1976 - Nascimento, Alexandre Vinícius Gonçalves (2016)
The marginal poetry, literary movement in the 1970s in Brazil, was legitimized by critics and some reference work on the subject as a literature 'antiliterária', 'anti-intellectual' and no proposal with the content and poetic elaboration. The term "generation mimeograph" strengthened an interpretation that qualified this literature as smaller and lower than the aesthetic standards recognized in the canonical selection of Brazilian literature. This paper aims to question the poetry label "alternative" given the marginal movement, seeking to understand it in the midst of production and cultivation present discussions in the 1970s in Brazil. For this, we take the anthology "26 poets today," 1976, as an object of this dissertation, from his poems and the performance of its writers, understanding the perception of paths of historical reality revealed by them. The issues surrounding the political positioning, the criticism of the authoritarian regime, the dialogue with the counterculture, with drugs, sexuality and taboo desires are subjects seized by poetic sensitivity of this generation, being privileged subjects for this work.